Quantifying the role of vapour pressure deficit in the development of lenticel breakdown in ‘Braeburn’ apple - Mzize, Nolubabalo (Stellenbosch : Stellenbosch University, 2021)
Thesis (MScAgric)--Stellenbosch University, 2021.